Przestrzeń filmowa jako przestrzeń wiedzy. O filmach Ray i Charlesa Eamesów - Świętochowska, Grażyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
Through the whole period of their design output, Ray and Charles Eames used film as a tool. First, they referred to film when they tried to prove their artistic activity, then for the purposes of advertisement and finally, they got to large, highly-circulated global multimedia projects. Behind them were state and corporate subjects. In all film activities, they reveal an innovative attitude which negotiated the current techniques of production. Each time, they were able to create new value. They revolutionized advertising and educational films. In every attempt at this genre, they did not give up the humanistic approach. They presented scientific knowledge, offered in the form of standard high entertainment.